Tratamento anaeróbio do líquido da casca de coco verde utilizando reator UASB - Araújo, Alex Miranda de (2008)
With the aim of reusing the agroindustry waste and aggregating value to the productive chain of immature coconut, Embrapa Agroindústria Tropical (Brazilian Agricultural Research Corporation, Tropical Agroindustry National Centre) has developed a system for processing this raw material. During the pressing stage, the Coconut Husk Liquor (CHL) is generated. It contains high concentration of organic matter, with Chemical Oxygen Demand (COD) varying from 60 to 80 g/L, including phenolic compounds and sugars. In this work, the performance of an Upflow Anaerobic Sludge Blanket Reactor (UASB) was evaluated for CHL treatment. The lab-scale UASB reactor (16.8 L) was operated during 222 days increasing the organic loading rate (OLR) from 2.2 kgCOD/m3.d to 10 kgCOD/m3.d. The UASB reactor performance was evaluated based on influent and effluent COD and total phenolic compounds (tannin); sludge specific methanogenic activity (SMA) and anaerobic toxicity; biogas production and composition; pH, alkalinity and volatile fatty acids (VFA). Results showed that UASB reactor can be used for pre-treatment of CHL, showing stability during the operation period, with COD removal efficiency higher than 80%, phenolics compounds removal efficiency of around 48%. The ratio AGV/alkalinity was always lower than 0,30. Biogas presented 75% of methane on its composition. Toxicity tests demonstrated that CHL was not toxic to the methanogenic consortia.